DYNAMICS OF ELECTRIC ENERGY POLICY THE COAL SECTOR IN INDONESIA: ANOMALY OR EXCEPTION? - Andreas Tedy Mulyono (NOMOI Law Review, 2021)
The dynamics of coal primary energy policy in Indonesia are still relevant to observe. On the one hand, coal commodity is a counter discourse in the mainstreem of green energy. On the other hand, the issue of the national electricity-energy crisis occurs due to obstruction of the primary energy supply chain. These two things are the challenge to the paradigm of energy resources as a capital for national development. Therefore, the issue of policy change in this case always needs to be studied. Analysis using normative juridical methods; in general related to the national energy policy and specifically on regulating coal mining to meet PLN's needs. The conclusion is that the prevailing laws and regulations have mandated the policy of national energy security. However, local utilization of coal needs to be regulated in a harmonious, transparent, and independent manner. The transparency and independence of coal primary energy development policies can be seen as an anomaly of the universal-global green energy paradigm. At least this is a temporary exception for Indonesia. Ensuring meeting our local's energy needs should be a priority for the next few decades.Keywords: Energy Policy, Coal Sector, Anomaly, Exception.